1975
DOI: 10.1161/01.str.6.2.160
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cerebral Infarction on the Regional Cerebral Blood Flow of the Contralateral Hemisphere

Abstract: Abstract:The Effect of Cerebral Infarction on the Regional Cerebral Blood Flow of the Contralateral Hemisphere• Regional cerebral blood flow (rCBF) measurements were performed over the contralateral hemisphere by the 133 Xe intracarotid injection method in 20 patients with acute cerebral infarction in the territory of the internal carotid artery. The rCBF was found to be reduced, sometimes remarkably, in all of the patients. The mean reduction was 30% to 36% from the lowest normal value for the mean age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 19 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…"• M~39 In patients with risk factors for atherothrombotic stroke (for example hypertension, diabetes mellitus, hyperlipidemia) the decrease in blood flow with increasing age is even more pronounced. 40 It has been demonstrated that the relation between age and cerebral blood flow was preserved under pathological conditions, for example in the case of cerebrovascular disease 41 and subarachnoidal hemorrhage. 42 In this study it was found that in most of the groups there was a correlation between age and ISI.…”
Section: Discussionmentioning
confidence: 99%
“…"• M~39 In patients with risk factors for atherothrombotic stroke (for example hypertension, diabetes mellitus, hyperlipidemia) the decrease in blood flow with increasing age is even more pronounced. 40 It has been demonstrated that the relation between age and cerebral blood flow was preserved under pathological conditions, for example in the case of cerebrovascular disease 41 and subarachnoidal hemorrhage. 42 In this study it was found that in most of the groups there was a correlation between age and ISI.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to absolute calculations, however, the relative approach requires comparison of each ROI with a "normal" reference region (usually within the contralateral hemisphere). The occurrence of perfusion disturbances in the contralateral hemisphere 36,37 makes the assumption that the contralateral hemisphere contains entirely normal tissue questionable. The latter constitutes a significant source of errors of relative perfusion measurements.…”
Section: Nabavi Et Al Perfusion Mapping Using Ct To Predict Cerebral mentioning
confidence: 99%
“…Some authors depend on cranial computed tomography (CT) and others on cerebral angiography to exclude patients with bilateral structural disease. 5 " 8 "~1 4 Since postmortem examination showed clinically unsuspected contralateral infarcts in some of these patients, 14 both techniques should be used to rule out bilateral infarcts and/or contralateral extracranial occlusive disease, either of which might explain the observed contralateral flow reduction. Prior studies also never controlled for other determinants of rCBF such as age, blood pressure, hematocrit, Pco 2 , and risk factors for stroke.…”
mentioning
confidence: 99%